EFFECT OF CROPPING SYSTEM AND SEASONAL VARIATION ON SOIL MICROBIAL BIOMASS AND ENZYMATIC ACTIVITIES IN ARID SOILS - R. Ullah; M. I. Lone; K. S. Ullah; S. M. Mehdi; M. A. Qazi (Journal of Animal and Plant Sciences, 2013)
Soil biological health is one of the best indicators for soil fertility thus plays a significant role in sustainability of cropping systems. In this regard, soil enzymes activities and microbial biomass have an important influence on nutrient cycling to sustain the soil fertility index. This study aimed to investigate the effects of different cropping systems and seasonal variations on soil microbial biomass and enzymatic activities in arid soils. For this purpose, soil samples were collected from the soils under wheat (Triticum aestivum)–maize (Zea mays L.) and wheat-mungbean (Vigna radiata) cropping systems. The data showed that the soil microbial biomass carbon (MBC), nitrogen (MBN), phosphorus (MBP) and soil enzymes such as dehydrogenase (DH) and alkaline phosphatase (AP) activities varied in all seasons. Overall, summer showed more soil MBC, MBN and MBP contents and relatively more DH and AP activities as compared to the other seasons. The soil MBC contents were higher under wheat-maize cropping system, while the soil MBN and MBP contents were higher under wheat-mungbean cropping systems in Kahuta areas. But the soil AP and DH activities were more pronounced under wheat-maize and wheat-mungbean cropping systems, respectively. We suggest that the inclusion of leguminous crops in cropping system is more suitable for arid areas, which tend to sustain soil fertility and preserve soil microbial biomass.
Keywords: Cropping systems; soil enzymes; arid environment; seasonal variations; soil microbial C; N and P contents